Innovative robot tool for full-automatic handling and wiring of deformable linear cables - Fröhlig, Simon; Nguyen, Huong Giang; Piechulek, Niklas; Franke, Jörg (Procedia CIRP, 2023)
The manufacturing of complex cable systems e.g. for vehicle integration or the direct wiring inside control cabinets is a laborious, manual, and error-prone process. For cost optimization reasons, cable pre-assembly is carried out in the best-cost countries. Long supply chains and a lack of resilience in the cable industry have recently caused the re-location of the final assembly of mechatronic products to high-automation countries. This paper presents a robot-guided tool that enables automated feeding, insertion, and routing of confectioned cables. We developed a gripping device to handle cables as damage-sensitive handling objects. The cable is pneumatically gripped by a flexible surface and clamped to absorb the forces during the insertion process. In contrast to state-of-the-art grippers which are based on rigid gripping jaws, we show that a force-locked gripping mechanism can be realized without damaging and imprinting the cable insulation. In this paper, both the design of the gripping tool and the insertion process flow are presented. We tested the tool with a Fanuc CR15-iA robot in the laboratory environment. Our experimental results proved the technical feasibility and led to the deduction of potential improvements for further research.
CRIS-Team Scopus Importer:2024-12-16
Keywords: automatic wiring; deformable linear object; DLO-in-hole; flexible gripper; wire assembly